The Effect of Financial Literacy and Service Quality on Preferences for Islamic Banks Through Interest as an Intervening Variable - Asih Handayani; Kharis Fadlullah Hana (AL-ARBAH: Journal of Islamic Finance and Banking, 2025)
Purpose - This study aims to determine the effect of Islamic financial literacy on financial behavior on student decisions to use Islamic banking products, with interest as an intervening variable. Method - This research uses a quantitative approach with the type of causality associative research, the data used is primary type with primary data obtained through distributing a 5-point Likert scale questionnaire to each respondent. Result - The results of this study found that financial literacy and service quality on usage decisions with student interest as an intervening variable had an insignificant effect. Student interest is also proven not to mediate the relationship between the two independent variables and usage decisions. Implication - This research involved active students of the Institut Agama Islam Negeri Kudus, Faculty of Islamic Business Economics, batch 2022-2024. Originality - These findings provide a basis for Islamic banking to improve education and services to encourage customer interest and loyalty, and enrich literature studies in the field of Islamic finance. Keywords:                     Literacy, Services, Interest, Decision, BSI